Value of Value based Education! - Mehta, Kunal (ISTORIA : Jurnal Pendidikan dan Ilmu Sejarah, 2022)
The paper in question  aims to study the meaning of the oft quoted and over exploited term "˜Value- based Education' . The other aim of this appear is to   understand how value -based education can bring a dramatic transformation in the life of an individual and how at the same time it can introduce  constructive changes in society. To seek answers to these questions, the paper studies the ancient system of education besides making an honest assessment of  the modern system of education .  The paper concludes that no' Education System' on this planet can succeed in its mission  if it delivers lessons sans ethics and values.